2012
DOI: 10.1542/peds.2012-0175
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and Costs of Health Care Use of Children With Medical Complexity

Abstract: Although a small proportion of the population, CMC account for a substantial proportion of health care costs. CMC make multiple transitions across providers and care settings and CMC with TA have higher costs and home care use. Initiatives to improve their health outcomes and decrease costs need to focus on the entire continuum of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
525
0
19

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 528 publications
(559 citation statements)
references
References 36 publications
15
525
0
19
Order By: Relevance
“…[1][2][3][4][5][6] In recent years, there has been a significant rise in innovative clinical programs targeting this population of children. 7 Health plans, children's hospitals, and other entities are enrolling high-cost children into care management programs to improve their health.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][6] In recent years, there has been a significant rise in innovative clinical programs targeting this population of children. 7 Health plans, children's hospitals, and other entities are enrolling high-cost children into care management programs to improve their health.…”
mentioning
confidence: 99%
“…[9][10][11][12][13] As for their adult counterparts, 14 hospital care is a significant contributor to the overall cost accrued by children with chronic conditions. 2,5,6 Many children who experience high health care costs incur frequent hospital admissions and lengthy hospitalizations. [15][16][17][18] Previous studies have reported that hospital care accounts for as much as 80% of total health care spending in children with severe chronic conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although estimates indicate they account for <1% of the pediatric population, children with medical complexity and technology dependence use almost one-third of all pediatric health care expenditures and make multiple transitions across providers and health care settings. 1,3,6,7 For instance, in 2006, children with medical complexity accounted for 10% of all US pediatric acute care hospital admissions, www.hospitalpediatrics.org 26% of pediatric hospital days, 40% of pediatric hospital charges, up to 92% of technology assistance procedures, and 435 inpatient deaths. 7 It has become imperative for health care providers to study and understand the needs of this population as models of care are developed.…”
Section: Discussionmentioning
confidence: 99%
“…Any conditions listed in the past medical history on either document were referenced to a previously published diagnostic list, which outlines complex-chronic diseases. 16 Conditions not listed on the list were then considered NCCs.…”
Section: Complexity and Chronicity Of Preexisting Conditionsmentioning
confidence: 99%